Increased P2X7 expression in the gastrointestinal tract and skin in a humanised mouse model of graft-versus-host disease. (27th January 2020) - Cuthbertson, Peter; Adhikary, Sam R.; Geraghty, Nicholas J.; Guy, Thomas V.; Hadjiashrafi, Amirazin; Fuller, Stephen J.; Ly, Diane; Watson, Debbie; Sluyter, Ronald
Abstract: Background: Allogeneic haematopoietic stem cell transplantation (HSCT) is a curative therapy for blood cancers; but results in the development of graft-versus-host disease (GVHD) in up to 70% of recipients. During GVHD, tissue damage results in ATP release into the extracellular compartment activating P2X7 on antigen-presenting cells, leading to the release of pro-inflammatory cytokines and subsequent activation of donor T cells. Therefore, the aim of the present study was to examine murine (m) P2rx7 and human (h) P2RX7 gene expression in GVHD target organs of humanised mice, and further characterise disease impact in these organs. Methods: NOD- scid IL2Rγ null (NSG) mice were injected with human peripheral blood mononuclear cells (hu-PBMC-NSG mice) or phosphate-buffered saline (PBS, control). Leucocytes were assessed by flow cytometry; gene expression was measured by quantitative polymerase chain reaction (qPCR), and tissue sections examined by histology. Results: Compared with control mice, hu-PBMC-NSG mice had increased m P2rx7 and m P2rx4 expression in the duodenum, ileum and skin. h P2RX7 was expressed in all tissues examined. hu-PBMC-NSG mice also displayed increased m Reg3g expression in the duodenum and ileum, despite limited histological gut GVHD. hu-PBMC-NSG mice showed histological evidence of GVHD in the skin, liver and lung. Compared with control mice, hu-PBMC-NSG mice displayed increased ear swelling. Conclusion: Combined data revealed that P2rx7 is up-regulated in gut and skin GVHD and that P2RX7 is present in target tissues of GVHD, corresponding to human leucocyte infiltration. Data also reveal increased m Reg3g expression and ear swelling in hu-PBMC-NSG mice, offering new measurements of early-stage gut GVHD and skin GVHD, respectively.